5 CORONIN 1B REGULATES HUMAN LUNG ENDOTHELIAL CELL GENERATION OF HYPEROXIA-INDUCED REACTIVE OXYGEN SPECIES. (1st March 2007) - Burns, M. P.; Pendyala, S.; Gorshkova, I. A.; He, D.; Bear, J. E.; Usatyuk, P. V.; Natarajan, V.
Abstract : Rationale: Coronins are a highly conserved family of WD repeat-containing actin binding proteins that regulate actin-dependent processes such as cell motility and endocytosis. We have demonstrated earlier that hyperoxia-induced activation of NADPH oxidase and reactive oxygen species (ROS) generation was regulated by tyrosine phosphorylation of cortactin, an actin binding protein in human pulmonary artery endothelial cells (HPAECs). Here we show that coronin 1B, an actin binding protein, negatively regulates hyperoxia-induced ROS production in HPAECs. Methods/Results: In HPAECs, coronin 1B is highly expressed as evidenced by real-time RT-PCR and Western blotting. Exposure of HPAECs to hyperoxia (95% O2 ) for 3 or 24 hours had no effect on the protein expression of coronin 1B. Coronin 1B was localized at the leading edge of the cell periphery and colocalized with cortactin in membrane ruffles under normoxia, and exposure to hyperoxia (3 hours) increased accumulation of coronin 1B and cortactin in membrane ruffles at the leading edge of the lamellipodia. Down-regulation of cortactin with cortactin siRNA partly attenuated hyperoxia-mediated ROS production; however, silencing coronin 1B with coronin 1B siRNA enhanced basal as well as hyperoxia-induced ROS accumulation (normoxia, scrambled siRNA, 100%; normoxia, coronin 1B siRNA, 301%; hyperoxia, scrambled siRNA, 379%; hyperoxia, coronin 1B siRNA, 452%). Conclusion: These results demonstrate that coronin 1B acts as a negative modulator of hyperoxia-induced ROS production and migration in lung endothelial cells. Supported by NIH grant HL PO1 058064 to V.N.